2021
DOI: 10.1002/cctc.202002077
|View full text |Cite
|
Sign up to set email alerts
|

Transacylation Kinetics in Fatty Acid and Polyketide Synthases and its Sensitivity to Point Mutations**

Abstract: Fatty acid and polyketide synthases (FASs and PKSs) synthesize physiologically and pharmaceutically important products by condensation of acyl building blocks. The transacylation reaction catalyzed by acyl transferases (ATs) is responsible for the selection of acyl‐CoA esters for further processing by FASs and PKSs. In this study, the AT domains of different multidomain (type I) PKS systems are kinetically described in their substrate selectivity, AT−Acyl carrier protein (ACP) domain‐domain interaction and enz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
18
0
4
Order By: Relevance
“…S1). We have recently demonstrated that the promiscuous AT domain from metazoan fatty acid synthase (FAS), termed malonyl-/acetyl transferase (MAT), is able to transfer various acyl-CoA moieties with high efficiencies 13 , different to AT domains from PKSs 14 . We hypothesized that this domain may also transfer fluorinated extender substrates into a PKS module, since FASs and PKSs are structurally and biochemically related (Fig 1b) [15][16][17] .…”
mentioning
confidence: 99%
“…S1). We have recently demonstrated that the promiscuous AT domain from metazoan fatty acid synthase (FAS), termed malonyl-/acetyl transferase (MAT), is able to transfer various acyl-CoA moieties with high efficiencies 13 , different to AT domains from PKSs 14 . We hypothesized that this domain may also transfer fluorinated extender substrates into a PKS module, since FASs and PKSs are structurally and biochemically related (Fig 1b) [15][16][17] .…”
mentioning
confidence: 99%
“…Parts of this chapter have been previously accepted for publication in: F. Stegemann, M. Grininger, "Transacylation Kinetics in Fatty Acid and Polyketide Synthases and its Sensitivity to Point Mutations", ChemCatChem (2021). [1] For individual contributions, copyright, and Creative Commons license, please see the statement of personal contributions.…”
Section: Resultsmentioning
confidence: 99%
“…All elution fractions contained other bands of lower molecular weight proteins. Since purification via tandem a nity chromatography usually results in pure protein, [1,17] these are most likely degraded proteins. The band of 170 kDa could correspond to the protein without KS-AT, the band at 60 kDa to KS-LD, and the band of 45 kDa to KS or LD-AT domains.…”
Section: Chimeric Mfas With Swapped Debs At5 and Raps At14mentioning
confidence: 99%
See 2 more Smart Citations